Roman Road Communication Epitauro-Resinum - Samardžić, Gligor M. (Collection of Papers of the Faculty of Philosophy in Priština, 2017)
In this paper, we present data on the Roman road communication Asamo-Epitauro-Reisinum (the present-day Trebinje-Cavtat-Risan), with the settlements along the route. From the road station Ad Zizio (the present-day village of Mosko or Ukšići in the area of Ljubomir) the road led south to Asamo (Trebinje), then over the road station Epitauro (Cavtat) to Resinum (Risan, or Rose). The archaeological finds (the remnants of a Roman settlement, road, fragments of  milestones) from the sites in Trebinje, Cavtat and Risan (the south of the province of Dalmatia) suggest that this area was, relatively early, connected with the network of Roman road communication. During the exploration of the ancient road communications and settlements in the south of the province of Dalmatia (southern Herzegovina, south-eastern Croatia, south-western Montenegro) we used original written sources and material remains from the site. Based on the visits to the sites in Trebinje, Cavtat and Risan, and the data obtained from oral sources as well, we believe that the road station Asamo is located in Trebinje, the road station Epitauro in Cavtat, and the road station Resinum in Risan, or Rose. Even though a significant number of findings is in favour of both of the thesis that the ancient Resinum is located in Risan, or Rose, systematic researches which would confirm this are yet to be conducted at this site.
Keywords: Resinum (Risan; or Rose); Epitauro (Cavtat); Asamo (Trebinje); the province of Dalmatia; Roman road communication